Multiple angiosarcomas of both breasts: a case report - Ryota Matsuda; Michiyo Saimura; Keisei Anan; Kento Katsuyama; Yuki Tahara; Kanako Kurata; Kohei Horioka; Mitsuhiro Nakamoto; Kenichiro Koga; Shoshu Mitsuyama; Eiichi Sato; Shinichi Wakamatsu; et al. (Surgical Case Reports, 2023)
Abstract Background Primary angiosarcomas of the breast are rare and highly aggressive. We herein report a rare case of multiple angiosarcomas detected concurrently in both breasts. Case presentation A 49-year-old woman visited a doctor after noticing a lump in her right breast. At that time, mammography and ultrasonography revealed no abnormal findings in either breast. She was referred to our hospital 5 months later, because screening mammography had revealed a focal asymmetric density in her right breast. Ultrasonography showed ill-defined hyper- and hypo-echoic lesions in both breasts. Magnetic resonance imaging disclosed five heterogeneously enhanced masses (5.8 cm in maximum diameter) in the right breast and six enhanced masses (approximately 1–3 cm in diameter) in the left breast. Histological examination of core needle biopsies revealed proliferation of irregularly shaped vascular channels lined by atypical endothelial cells throughout the adipose tissue and lobules of the breasts, leading to a diagnosis of well-differentiated angiosarcoma. The lesions were assumed to be primary angiosarcomas, because she had neither a history of breast surgery nor of radiation therapy. She underwent bilateral mastectomies and postoperative chest wall irradiation. Computed tomography 11 weeks after the surgery revealed multiple, small, subcutaneous nodules in the chest wall that were suspected of being angiosarcoma metastases. We started chemotherapy (weekly paclitaxel 80 mg/m2), which achieved shrinkage of these nodules within 2 months. Conclusions Early diagnosis, immediate initiation of local and systemic therapies, and intensive follow-up are important in improving the prognosis of angiosarcomas.